Baked egg tolerance: is it possible to predict? - Lisis Karine Vilar; Pedro Rocha Rolins Neto; Mariana Amorim Abdo; Marina Fernandes Almeida Cheik; Christiane Pereira e Silva Afonso; Gesmar Rodrigues Silva Segundo (Jornal de Pediatria (Versão em Português), 2020)
Objective: To assess the frequency of baked egg tolerance in IgE‐mediated egg allergy patients through the oral food challenge and to assess the tolerance predictability of different skin prick tests, as well as specific serum IgE measurement to egg proteins. Methods: In this cross‐sectional study, 42 patients with a diagnosis of egg allergy were submitted to different skin prick tests with egg (in natura, boiled, muffin, ovalbumin, and ovomucoid), and specific IgE to egg white, ovalbumin, and ovomucoid; as well as to the oral food challenge with food containing egg, extensively baked in a wheat matrix. Results: Of the total, 66.6% of patients tolerated the ingestion of egg‐containing foods in the oral food challenge. A comparative analysis with positive and negative oral food challenge found no significant differences regarding age, gender, other food allergies, or even specific skin prick tests and IgE values between the groups. Conclusions: The study demonstrated an elevated frequency of baked egg food‐tolerant individuals among egg allergy patients. None of the tested markers, skin prick tests, or specific IgE, were shown to be good predictors for identifying baked egg‐tolerant patients. The oral food challenge with egg baked in a matrix is central to demonstrate tolerance and the early introduction of baked foods, improving patients’ and families’ quality of life and nutrient intake. Resumo: Objetivo: Avaliar a frequência de tolerância a alimentos assados com ovo em pacientes com alergia ao ovo mediada por IgE por meio do teste de provocação oral e verificar a capacidade de predição de tolerância ao ovo por meio de teste cutâneo de leitura imediata (Skin Prick Test ou SPT) e de dosagem sérica de IgE específica para componentes do ovo. Métodos: Estudo transversal, 42 pacientes com diagnóstico de alergia ao ovo foram submetidos a SPT com ovo (in natura, cozido, bolinho, ovoalbumina e ovomucoide), IgE específica para clara de ovo, ovoalbumina e ovomucoide e ao teste de provocação oral com alimento com ovo extensamente assado em matriz de trigo. Resultados: Dos pacientes, 66,6% toleraram a ingestão do alimento com ovo durante o teste de provocação oral. Não encontramos diferenças em relação a idade, gênero, outras alergias alimentares ou mesmo entre os valores dos SPT e IgE específica na análise comparativa entre os grupos com teste de provocação oral positivo e teste de provocação oral negativo. Conclusões: Foi demonstrada uma elevada frequência de indivíduos tolerantes a ingestão de alimentos assados com ovo entre os pacientes com alergia a ovo mediada por IgE. Nenhum dos marcadores testados, SPT ou IgE específica, demonstrou ser bom preditor para identificar os pacientes tolerantes. Consideramos que os testes de provocação oral com alimentos com ovo assado sejam fundamentais para a introdução desses assados, melhorar a qualidade de vida e a ingestão de nutrientes dos pacientes e famílias.